Preparation of genetically or chemically engineered exosomes and their therapeutic effects in bone regeneration and anti-inflammation - Wang, Xinyue; Gong, Weitao; Li, Rongrong; Li, Lin; Wang, Jing (Frontiers in Bioengineering and Biotechnology, 2024)
The treatment of bone or cartilage damage and inflammation-related diseases has been a long-standing research hotspot. Traditional treatments such as surgery and cell therapy have only displayed limited efficacy because they can't avoid potential deterioration and ensure cell activity. Recently, exosomes have become a favorable tool for various tissue reconstruction due to their abundant content of proteins, lipids, DNA, RNA and other substances, which can promote bone regeneration through osteogenesis, angiogenesis and inflammation modulation. Besides, exosomes are also promising delivery systems because of stability in the bloodstream, immune stealth capacity, intrinsic cell-targeting property and outstanding intracellular communication. Despite having great potential in therapeutic delivery, exosomes still show some limitations in clinical studies, such as inefficient targeting ability, low yield and unsatisfactory therapeutic effects. In order to overcome the shortcomings, increasing studies have prepared genetically or chemically engineered exosomes to improve their properties. This review focuses on different methods of preparing genetically or chemically engineered exosomes and the therapeutic effects of engineering exosomes in bone regeneration and anti-inflammation, thereby providing some references for future applications of engineering exosomes.